2011
DOI: 10.1002/mnfr.201100380
|View full text |Cite
|
Sign up to set email alerts
|

Bilberries and their anthocyanins ameliorate experimental colitis

Abstract: Bilberries have positive effects in acute and chronic diarrhea. Patients with inflammatory bowel disease (IBD) report on improved symptoms upon ingestion. Bilberries contain approximately 10% of anthocyanins (ACs), which have anti-oxidative, anti-carcinogenic, and anti-inflammatory properties. We investigated whether experimental colitis can be ameliorated by dried bilberries or ACs. Acute and chronic dextrane sodium sulphate (DSS) colitis were induced in Balb/c mice by 2.5% DSS in the drinking water. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 15 publications
2
42
0
2
Order By: Relevance
“…The findings on the prevention of colonic inflammation induced by DSS are in line with earlier experiments of our lab where we could demonstrate that anthocyanins have anti-inflammatory properties and ameliorate DSSinduced chronic colitis [27] . In human monocytic THP-1 cells, bilberry extract reduced interferon-γ (IFN-γ)-induced signal protein activation, pro-inflammatory gene expression and cytokine secretion, and enhanced tumor necrosis factor-α (TNF-α)-induced responses [28] .…”
Section: Discussionsupporting
confidence: 81%
“…The findings on the prevention of colonic inflammation induced by DSS are in line with earlier experiments of our lab where we could demonstrate that anthocyanins have anti-inflammatory properties and ameliorate DSSinduced chronic colitis [27] . In human monocytic THP-1 cells, bilberry extract reduced interferon-γ (IFN-γ)-induced signal protein activation, pro-inflammatory gene expression and cytokine secretion, and enhanced tumor necrosis factor-α (TNF-α)-induced responses [28] .…”
Section: Discussionsupporting
confidence: 81%
“…It has been previously demonstrated that anthocyanins from bilberries decrease pro-inflammatory cytokine serum levels and attenuate the severity of experimental colitis in mice [11,12,13]. Here, we have shown that BE clearly inhibits the pro-inflammatory effects of IFN-γ in human THP-1 monocytes as well as in human PBMCs.…”
Section: Discussionsupporting
confidence: 50%
“…A number of studies showed that polyphenols attenuate disease activity in IBD patients [11,12,13,14]. The aim of this cell culture model was to provide more information about the cellular mechanisms underlying the protective and anti-inflammatory properties of anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrakte aus der Heidelbeere finden sich auch als Zusatz zu bilanzierten Glucose-Elektrolyt-Lösungen; die darin enthaltenen Anthocyanidine [3] wirken reizlindernd, entzündungshemmend und adstringierend. Bei Obstipation, die vor allem im Kleinkindesalter zunehmend beobachtet wird, müssen nicht immer synthetische Laxantien oder Klysmen zum Einsatz kommen.…”
unclassified